The art of cardiovascular risk assessment. Issue 5 (10th May 2018) - Khambhati, Jay; Allard‐Ratick, Marc; Dhindsa, Devinder; Lee, Suegene; Chen, John; Sandesara, Pratik B.; O'Neal, Wesley; Quyyumi, Arshed A.; Wong, Nathan D.; Blumenthal, Roger S.; Sperling, Laurence S.
Abstract : Cardiovascular disease (CVD) remains the leading cause of death in the United States. Healthcare expenditures have been principally allocated toward treatment of CVD at the end of the health/disease continuum, rather than toward health promotion and disease prevention. A focused effort on both primordial and primary prevention can promote cardiovascular health and reduce the burden of CVD. Risk‐factor assessment for predicting atherosclerotic CVD events serves as the foundation of preventive cardiology and has been driven by population‐based scoring algorithms based on traditional risk factors. Incorporating individual nontraditional risk factors, biomarkers, and selective use of noninvasive measures may help identify more at‐risk patients as well as truly low‐risk individuals, allowing for better targeting of treatment intensity. Using a combination of validated population‐based atherosclerotic CVD risk‐assessment tools, nontraditional risk factors, social health determinants, and novel markers of atherosclerotic disease, we should be able to improve our ability to assess CVD risk. Through scientific evidence, clinical judgment, and discussion between the patient and clinician, we can implement an effective evidence‐based strategy to assess and reduce CVD risk.